The Influence of Digital Marketing on Domino's Pizza Purchasing Decisions in Mojokerto City - Dea Vike Permata Sari; Rahayu; M Syamsul Hidayat (CV Putra Publisher, 2023)
The presence of the internet, which has been used by almost all Indonesian people, both in cities and villages, is able to provide new opportunities for companies, including restaurant companies. Domino's Pizza is one of the fast food outlets from the United States which is quite well known in Indonesia. Domino's Pizza serves a variety of fast food and as the name implies the main menu of this outlet is Pizza. As a multinational company, of course Domino's Pizza has an adequate digital marketing plan. This research uses descriptive quantitative method. With a sample of Domino's Pizza Mojokerto consumers as many as 100 respondents and tested using SPSS 25. The results showed that the website had a significant and positive effect on the purchase decision of Domino's Pizza Mojokerto with a regression coefficient b of 0.226, Instagram had a significant and positive effect on the purchase decision of Domino's Pizza Mojokerto with the value of the regression coefficient b is 0.351, and Facebook has a significant and positive effect on the purchase decision of Domino's Pizza Mojokerto with a regression coefficient b of 0.212.